2011
DOI: 10.3904/kjim.2011.26.4.466
|View full text |Cite
|
Sign up to set email alerts
|

An Adult Case of Chronic Active Epstein-Barr Virus Infection with Interstitial Pneumonitis

Abstract: Chronic active Epstein-Barr virus (CAEBV) infection is characterized by persistent infectious mononucleosis-like symptoms, an unusual pattern of Epstein-Barr virus (EBV) antibodies, detection of the EBV genome in affected tissues or peripheral blood, and chronic illness that cannot be attributed to any other known disease. This is the first reported Korean case of an immunocompetent adult with CAEBV-associated interstitial pneumonitis. A 28-year-old female was admitted with a fever that persisted for 3 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In that case, TCRγ gene rearrangement exhibited a polyclonal pattern, unlike that observed in our case. That finding indicates that the case reported by Joo et al [4] was a case of CAEBV infection that had not progressed to monoclonal LPD. Typically, EBV-associated LPDs are derived from B-cell diseases, such as Hodgkin's lymphoma or Burkitt's lymphoma, and are a well-established phenomenon in patients with primary or secondary immunodeficiencies [2].…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In that case, TCRγ gene rearrangement exhibited a polyclonal pattern, unlike that observed in our case. That finding indicates that the case reported by Joo et al [4] was a case of CAEBV infection that had not progressed to monoclonal LPD. Typically, EBV-associated LPDs are derived from B-cell diseases, such as Hodgkin's lymphoma or Burkitt's lymphoma, and are a well-established phenomenon in patients with primary or secondary immunodeficiencies [2].…”
supporting
confidence: 69%
“…In Korea, Joo et al [4] recently reported a case of CAEBV infection with interstitial pneumonitis in a young woman. She recovered spontaneously and exhibited a good clinical course.…”
mentioning
confidence: 99%
“…Rarer forms of CAEBV include: pancytopaenia, CNS involvement, intracranial calcifications, inflammation of the salivary glands, sinusitis, and oral mucosal ulcerations [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial pneumonia is a diffused chronic interstitial lung disease associated with inflammation and/or fibrosis of the alveolar walls [ 10 ]. Three pulmonary manifestations associated with EBV infection: hilar/mediastinal lymphadenopathy, pleural effusion, and IP have been described in literature [ 5 ]. EBV-associated IP may be triggered by drugs, occupational exposure, hypersensitivity reactions and infections; some cases are, however, idiopathic [ 11 ].…”
Section: Discussionmentioning
confidence: 99%